2003
DOI: 10.1182/blood-2003-01-0338
|View full text |Cite
|
Sign up to set email alerts
|

Classification of pediatric acute lymphoblastic leukemia by gene expression profiling

Abstract: Contemporary treatment of pediatric acute lymphoblastic leukemia (ALL) requires the assignment of patients to specific risk groups. We have recently demonstrated that expression profiling of leukemic blasts can accurately identify the known prognostic subtypes of ALL, including T-cell lineage ALL (T-ALL), E2A-PBX1, TEL-AML1, MLL rearrangements, BCR-ABL, and hyperdiploid karyotypes with more than 50 chromosomes. As the next step toward developing this methodology into a frontline diagnostic tool, we have now an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
478
5
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 517 publications
(531 citation statements)
references
References 35 publications
40
478
5
8
Order By: Relevance
“…For these analyses, we focused on the 52 patients with B-lineage ALL to avoid a distortion of results solely based on gene expression differences between ALL immunophenotypes. Pronounced differences in gene expression profiles between B-and T-lineage ALL have been described before and were confirmed by our data, supporting the notion that these ALL subtypes represent distinct biological and clinical entities (10,12).…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…For these analyses, we focused on the 52 patients with B-lineage ALL to avoid a distortion of results solely based on gene expression differences between ALL immunophenotypes. Pronounced differences in gene expression profiles between B-and T-lineage ALL have been described before and were confirmed by our data, supporting the notion that these ALL subtypes represent distinct biological and clinical entities (10,12).…”
Section: Resultssupporting
confidence: 77%
“…Therefore, we asked whether those gene expression signatures that predict genetic and immunologic subtypes in initial ALL (10,12) could also faithfully classify relapse samples based on the present analysis. To this end, published data from 104 initial ALL patients (10) were used as training set to recalculate the diagnostic signatures of the ALL subtypes shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 In gene expression profiling (GEP) studies, MLL-rearranged cases clustered together as one group in AML as well as in ALL. 13,[62][63][64] However, our laboratory showed that within MLL-rearranged infant ALL each type of MLL translocation is associated with a translocation-specific gene expression signature. 65 We identified a specific gene expression signature for the total group of MLL-rearranged AML cases, 12 but were also able to identify a specific signature for t(9;11)(p22;q23).…”
Section: Epidemiology Of Mll Aberrations In Pediatric Amlmentioning
confidence: 90%
“…Three (trisomy) or four (tetrasomy) copies of chromosome 21 is common in childhood acute lymphoblastic leukemia (ALL) [2][3][4]. Children with Down syndrome (DS) who carry trisomy 21 in all their cells have a 20-fold increased risk for childhood ALL and 600-fold risk for acute megakaryocytic leukemia (AMKL) [5].…”
Section: Aneuploidy Of Chromosome 21 and Acute Megakaryocytic Leukemiamentioning
confidence: 99%